(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Reproductive health refers to the sexual system of men and women at all stages of life. In women, the ovaries, and in men, the testes, are sexual organs or glands that maintain the health of their respective systems. Women working in the sewing industry face a number of production factors that negatively affect their health and functions. These factors include noise, vibration, increased levels of electromagnetic radiation, unfavorable lighting conditions, and forced working postures. As a result, employees in this field often develop diseases of the circulatory, respiratory, endocrine, and musculoskeletal systems. There is also information about frequent gynecological pathologies, pregnancy and childbirth complications, malignant tumors, and premature aging of the body among women working in the textile industry.